Impact of late follicular luteinizing hormone levels on live birth rate after fresh embryo transfer: a retrospective cohort study in GNRH antagonist cycles - Jelassi, Nada; Zimmermann, Appoline; Faust, Cindy; Miquel, Laura; Buffat, Christophe; Perrin, Jeanne; Courbiere, Blandine (Frontiers in Endocrinology, 2025)
ObjectiveTo investigate the impact of LH levels in the late follicular phase during the GnRH antagonist protocol on embryo implantation and IVF live birth rate (LBR) after fresh embryo transfer (ET).DesignRetrospective cohort study.SubjectsWomen who underwent controlled ovarian stimulation (COS) with a GnRH antagonist protocol at a Reproductive Medicine Center in a University Teaching Hospital between January 2020 and December 2022.ExposureMonocentric study involving 544 IVF cycles with the GnRH antagonist protocol. Four groups were stratified based on preovulatory LH levels: Q1: LH < 25th percentile, Q2: LH 25-50th percentile, Q3: LH 50-75th percentile, and Q4: LH > 75th percentile.Main outcome measuresThe primary outcome was the live birth rate after fresh embryo transfer. Secondary outcomes included embryo implantation, clinical pregnancy, and early pregnancy loss rates.ResultsDuring the late follicular phase, estradiol levels were significantly correlated with preovulatory LH levels (P = 0.03). The number of retrieved oocytes, 2PNs (two pronuclei), and usable embryos were similar across the groups. No significant differences were observed between the groups regarding implantation rate, clinical pregnancy rate, early pregnancy loss, and LBR (P > 0.05).ConclusionIn the antagonist protocol, pre-ovulatory LH levels had no impact on embryo implantation or IVF outcomes. A low LH level in the late follicular phase is not an indication for embryo freeze-all.